Gimbusowa kultura dziecięca – rekonesans badawczy - Marzenna Nowicka; Anita Lodd-Bartołd (Problemy Wczesnej Edukacji)
The article presents the results of an ethnographic study on the manifestations of children’s peer culture generated in school gimbus. The methods of obtaining data were participant interviews. Based on them, reconstructed elements of peer culture in the field of forms of gimbus activity. Specific features of children’s communication were also identified, which included: age separation, concentration on school problems, genre of subjects, showing off, using dialect.